2009
DOI: 10.1149/1.3099679
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry of an Anti-cancer Drug

Abstract: Voltammetric oxidation of vinblastine sulfate was studied at the platinum semi-micro electrode, by cyclic and pulsed voltammetric techniques, in 9:1 acetonitrile-water mixture containing 0.2 M sodium perchlorate. A plausible scheme of sequential electrochemical and chemical reactions is suggested for the cyclic voltammetric behavior of vinblastine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…On the other hand, despite the redox active groups in the molecular structure of Vinca alkaloids, very few studies have been reported on their electrochemical properties due to their very complex structure [9-15]. Considering that voltammetry, which is one of the electroanalytical methods, is simple, fast, low cost, low sensitive to matrix effect and suitable for on-site analysis; it is clear that this method will be an alternative candidate for the determination of these antineoplastic drugs in the near future [16][17][18].…”
Section: Article Info Abstractmentioning
confidence: 99%
“…On the other hand, despite the redox active groups in the molecular structure of Vinca alkaloids, very few studies have been reported on their electrochemical properties due to their very complex structure [9-15]. Considering that voltammetry, which is one of the electroanalytical methods, is simple, fast, low cost, low sensitive to matrix effect and suitable for on-site analysis; it is clear that this method will be an alternative candidate for the determination of these antineoplastic drugs in the near future [16][17][18].…”
Section: Article Info Abstractmentioning
confidence: 99%